EFFICACY OF POULTRY LITTER AS A SOURCE OF NUTRIENT FOR THE BIOREMEDIATION OF TOTAL PETROLEUM HYDROCARBON CONTAMINATED TROPICAL BUNKERING SITE - USESE, A. I. (UNILAG Journal of Medicine, Science and Technology, 2019)
Contamination of soils with total petroleum hydrocarbon (tph) is a wide spread environmental problem requiring urgent remedial action and controls. This study evaluates the effectiveness of poultry litter for ex-situ bioremediation of total petroleum hydrocarbon (tph) contaminated soils. Four treatment groups in replicates consisting of 1 kg of soils was amended with poultry litre. Minimal salt medium was also included to enhance the rate of bioremediation at a temperature of 250c to 300c over a six week period. The levels of tph concentration was monitored by gas chromatography (gc) after extraction with n-hexane. The result showed that at optimal conditions, the tph removal efficiency of poultry litter and minimal salt composites reached 60.9% of the initial value. Corresponding tph removals were obtained as 37%, 44% and 42.9% respectively for other treatment options, demonstrating potential efficiency of poultry litter as co-substrate and source of inorganic nutrients for ex-situ bioremediation of petroleum compounds. At 10% by volume of dry weight sample, poultry litter increased the bacterial biomass and reduced the time necessary for biodegradation significantly (p>0.05). It was also observed that a mixed culture of bacterial (bacillus and pseudomonas) and fungal (trichoderma, fusarium and aspergillus) strains demonstrated more stable growth behavior and degraded the contaminants to much lower concentrations. The results of gc profiles also revealed that soil samples unamended with nutrients were the least degraded. This finding emphasises the need for nutrient amendment and environmentally friendly intervention strategies in the bioremediation of soils adversely impacted by tph.